Experimental investigations of fabric material against projectile impacts. (1st February 2016) - Chen, Wensu; Hao, Hong; Irawan, Paulus; Chen, Shuyang; Meng, Qingfei
Graphical abstract: The structural response to windborne debris impact of PVC coated fabric material for air supported structure construction is the first study in the literature. Highlights: PVC coated polyester fabric material against debris impact was studied. Tests were carried out by using a pneumatic cannon testing system. The failure and damage modes of specimens were observed and discussed. Penetration resistance capacity of fabric against debris impacts was identified. Abstract: Air supported structures made of PVC coated polyester fabric materials have been used in industrial and commercial building constructions. If they are used in cyclonic regions, the structure envelop might be impacted by windborne debris. The windborne debris might perforate the fabric material, which not only results in total collapse of the structure, flying debris at high speed also imposes threats to people and facilities inside the structure. In this study, the penetration resistant capability of PVC coated polyester fabric material commonly used in air supported structures construction was tested by using a pneumatic cannon system. The impact loading from windborne debris equivalent to a timber projectile of 4 kg mass as specified in the Australian Wind Loading Code (AS/NZS 1170.2:2011) was applied in the test. The failure and damage modes under various projectile impact scenarios were observed and compared. Its capability of resisting projectile impact was assessed. The performances of PVC coated polyester fabric material were examined quantitatively in terms of projectile residual velocity and energy absorption. The effects of various projectile velocity, impact location, fabric pretension and boundary condition on their penetration resistance performance were studied. The testing results will benefit construction designers involved in the fabric material applications in high wind speed area.